The Effects of IFRS Compliance on Earnings Reporting Quality of Financial Firms in Ghana - Coffie, William; Bedi, Ibrahim; Amidu, Mohammed; Duah, Bernard Baah (Journal of Accounting and Finance, 2020)
We investigate whether compliance with International Financial Reporting Standards (IFRS) is associated with earnings reporting quality of financial firms operating in Ghana. We modelled earnings reporting quality as a function of IFRS compliance and relevant control variables. Contrary to our hypothesis, IFRS compliance has a positive coefficient with our earnings management proxy for reporting quality. Our result suggests that IFRS does not necessarily improve the quality of financial reporting among Ghanaian financial firms. The result contradicts the idea that IFRS adoption eliminates accounting alternatives. Our results demonstrate that the compulsory adoption of IFRS by financial firms in Ghana has not improved reporting quality.